2005
DOI: 10.1177/1545968305282269
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Grip Force Modulation in the Ipsilesional Hand after Unilateral Middle Cerebral Artery Stroke

Abstract: Understanding grasping control after stroke is important for relearning motor skills. The authors examined 10 individuals (5 males; 5 females; ages 32-86) with chronic unilateral middle cerebral artery (MCA) stroke (4 right lesions; 6 left lesions) when lifting a novel test object using skilled precision grip with their ipsilesional ("unaffected") hand compared to healthy controls (n = 14; 6 males; 8 females; ages 19-86). All subjects possessed normal range of motion, cutaneous sensation, and proprioception in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
58
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 68 publications
6
58
0
Order By: Relevance
“…Impaired isometric strength and force control in the lessaffected knee extensors are consistent with previously reported bilateral changes after stroke (31,34,36,43,47,58,66). Several factors may contribute to impaired motor function of the less-affected limbs, including hemispheric lateralization for the executed tasks and hemispheric asymmetry (36) or evolving maladaptive changes in the intact hemisphere (38).…”
Section: Discussionsupporting
confidence: 87%
“…Impaired isometric strength and force control in the lessaffected knee extensors are consistent with previously reported bilateral changes after stroke (31,34,36,43,47,58,66). Several factors may contribute to impaired motor function of the less-affected limbs, including hemispheric lateralization for the executed tasks and hemispheric asymmetry (36) or evolving maladaptive changes in the intact hemisphere (38).…”
Section: Discussionsupporting
confidence: 87%
“…Patients with a unilateral left hemisphere stroke (LHS) and elderly controls used their non-dominant, left (ipsilesional) hand to grasp and move an object once in context L, which represents a typical laboratory task, and once in context E, which was modeled after many activities of everyday life. The current data confirm that kinematics and dynamics of reach-to-grasp movements strongly differ between contexts (Bock and Baak, 2013;Bock and Steinberg, 2012;Bock and Züll, 2013), that ipsilesional movements of non-apraxic patients with LHS are impaired (Quaney et al, 2005;Sunderland et al, 1999;Winstein and Pohl, 1995;Goodale, 1988), and that the deficient coordination between the transport and the grasp component is an essential aspect of this impairment (Lang et al, 2005;Nowak et al, 2007aNowak et al, , 2007b.…”
Section: Discussionsupporting
confidence: 78%
“…Functional imaging studies show that complex motor tasks requiring motor planning, integration of sensorimotor information and attention to sequencing are associated with bi-hemispheral activity 2730. In general, more complex unilateral motor tasks such as the 9HPT induce greater bilateral task related activity than do simple tasks3133 and, indeed, with the exception of an older study by Colebatch and Gandevia which identified a reduction in strength in the ipsilateral hand in 14 subacute-to-chronic stroke patients,4 most other behavioural studies have identified post-stroke ipsilateral deficits in complex functions—target directed movements of the hand and foot,5 abnormal anticipated grip forces when lifting novel test objects,34 step tracking deficits in the wrist8 and slowing on the 9HPT7 and grooved pegboard test 35. Among the studies that measured ipsilateral hand function over time, Jones et al , who assessed eight patients with unilateral stroke at six time points starting from day 11 and ending at 12 months post stroke,11 found persistently impaired reaction time, impairment of steadiness and tracking on visuomotor tasks in the ipsilateral hand but no ipsilateral weakness.…”
Section: Discussionmentioning
confidence: 99%